Listening to the green voices of the elderly: A qualitative exploration of satisfaction with age-friendly recreational landscapes in residential green spaces - Wang, Fanglong; Hussain, Norhuzailin; Abdul Aziz, Faziawati (Routledge, 2024)
The study focuses on Lianyungang City, China, a context that provides valuable insights into factors influencing the design of aging-friendly recreational landscapes in residential green spaces. It is essential to enhance the refurbishment of such areas and give older adults healthy and enjoyable outdoor spaces. The research conducted 31 semi-structured interviews, employing coding analysis with the assistance of qualitative analysis software NVivo12Plus and utilizing the rootedness theory. The study identified six core influencing factors and 23 constituent factors that impact satisfaction with aging-friendly recreational landscapes in residential green spaces. Coding analysis revealed that recreational facilities, community participation, management, green space design, microclimate, and safety are the six main influencing factors. Recreational facilities were the most significant influence on satisfaction with aging-friendly recreational landscapes in residential green spaces. At the same time, community participation was crucial in influencing satisfaction with these landscapes. Finally, the article offers recommendations for optimizing aging-friendly recreational landscapes in China’s residential green spaces, considering the context of China’s aging society. © 2024 Taylor & Francis Group, LLC.